Audialna przestrzeń mediów - Skrzydlewski, Wojciech (Wydawnictwo Naukowe UAM, 2012)
The article discusses the issues of popular culture research areas, in particular the audio sphere rendered in the media. It describes the meaning of music journalism in traditional and new media, and brings attention to different aspects of music functioning in cyberspace in the context of authoraudience exchange of roles.
The audio space of media